LINC01117 inhibits invasion and migration of lung adenocarcinoma through influencing EMT process. - Linjun Liu; Wenjia Ren; Licheng Du; Ke Xu; Yubai Zhou (PLoS ONE, 2023)
Background Studying the mechanism of action of LncRNAs in lung adenocarcinoma (LUAD) is of great importance for an in-depth understanding of the molecular mechanism of lung adeno carcinogenesis and development. Objective The aim is to identify a long non-coding RNA LINC01117 that is specifically and highly expressed in LUAD cells and to investigate its biological functions and molecular mechanisms in LUAD cells, providing a new potential target for targeting LUAD therapy. Methods This study used publicly available data downloaded from The Cancer Genome Atlas (TCGA) database. Construction of siRNA and overexpression plasmid-packed lentiviral constructs were used to knock down and increase the expression of LINC01117 in LUAD cells. The effect of LINC01117 on LUAD cell migration and invasion was verified by scratch assays and Transwell assays. Western blot assays were performed to verify the effect of knocking down LINC01117 expression on key proteins of the EMT process. The effect of overexpression and knockdown LINC01117 expression on key proteins of the EMT process and the nuclear and cytoplasmic distribution of YAP1, a key effector molecule of the Hippo pathway, was verified by Western blot assays. Results LINC01117 expression was upregulated in LUAD tissues and cell lines. Clinical correlation and prognostic analyses showed that LINC01117 was associated with poorer clinical features (staging and N classification) and poorer prognosis and could be analyzed as an independent prognostic factor. Cell migration and invasion were significantly inhibited in the knockdown group compared to the control group; in contrast, cell migration and invasion were promoted in the overexpression group. Overexpression of LINC01117 resulted in down-regulation of E-cadherin expression and increased expression levels of N-cadherin, vimentin, ZEB1, snail and slug; in contrast, knockdown of LINC01117 appeared to have the opposite effect. Furthermore, knockdown of LINC01117 increased the enrichment of YAP1 protein in the cytoplasm and reduced its level in the nucleus; overexpression of LINC01117 produced the opposite intracellular distribution results. Conclusions LINC01117 was highly expressed in LUAD, and knockdown of LINC01117 significantly inhibited the migration and invasion of LUAD cells, while overexpression of LINC01117 significantly promoted the migration and invasion of LUAD cells, and affected the EMT process, and was able to alter the distribution of YAP1 in the nucleus and cytoplasm. This suggests that LINC01117 may regulate the activity of the Hippo pathway by altering the nuclear and cytoplasmic distribution of YAP1, which in turn induces the EMT process in lung adenocarcinoma cells and thus exerts a pro-cancer effect. It suggests that LINC01117 may play a key role in the occurrence and development of LUAD.